2022
DOI: 10.3390/s22249574
|View full text |Cite
|
Sign up to set email alerts
|

Deep Deterministic Policy Gradient-Based Autonomous Driving for Mobile Robots in Sparse Reward Environments

Abstract: In this paper, we propose a deep deterministic policy gradient (DDPG)-based path-planning method for mobile robots by applying the hindsight experience replay (HER) technique to overcome the performance degradation resulting from sparse reward problems occurring in autonomous driving mobile robots. The mobile robot in our analysis was a robot operating system-based TurtleBot3, and the experimental environment was a virtual simulation based on Gazebo. A fully connected neural network was used as the DDPG networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The network model outputs continuous linear and angular velocities to control the robot’s forward movement and steering. The and the previous action serve as state input, enabling the neural network to gauge the robot’s speed and its distance from the target [ 34 ]. It is pertinent to highlight that represents the Euclidean distance between the target coordinates and the current robot coordinates , which is defined as follows: …”
Section: Methodsmentioning
confidence: 99%
“…The network model outputs continuous linear and angular velocities to control the robot’s forward movement and steering. The and the previous action serve as state input, enabling the neural network to gauge the robot’s speed and its distance from the target [ 34 ]. It is pertinent to highlight that represents the Euclidean distance between the target coordinates and the current robot coordinates , which is defined as follows: …”
Section: Methodsmentioning
confidence: 99%
“…They test and validate their approach using the CARLA simulator [25]. However, Park et al, apply the deep deterministic policy gradient (DDPG) path-planning method for mobile robots using Gazebo simulator [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The technology applied in this study was previously introduced in the authors’ earlier work [ 23 ]. In [ 23 ], a method integrating the HER technique to assist in finding the optimal policy was proposed and demonstrated its effectiveness in both simulation and real-world environments without obstacles.…”
Section: Preliminariesmentioning
confidence: 99%
“…The agent was trained in a simple driving environment within the simulation. We demonstrated that the proposed method operates effectively in both simulated and actual environments [ 23 ]. The HER has also been widely applied in the fields of mobile robotics and robot arm control [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%